2014
DOI: 10.1016/j.febslet.2014.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Roles of intraloops‐2 and ‐3 and the proximal C‐terminus in signalling pathway selection from the human calcium‐sensing receptor

Abstract: Edited by Ned ManteiKeywords: Calcium-sensing receptor G-protein coupled receptor Biased signalling Phosphatidylinositol-specific phospholipase-C Adenosine 3 0 ,5 0 -cyclic monophosphate ERK 1/2 a b s t r a c tThe calcium-sensing receptor (CaSR) couples to signalling pathways via intracellular loops 2 and 3, and the C-terminus. However, the requirements for signalling are largely undefined. We investigated the impacts of selected point mutations in iL-2 (F706A) and iL-3 (L797A and E803A), and a truncation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 38 publications
5
22
0
Order By: Relevance
“…Similarly, although both Ca 2+ o and L‐phenylalanine stimulated Ca 2+ i mobilization in CaS receptor‐transfected HEK293 cells, only Ca 2+ o promoted IP accumulation and diacylglycerol production (Rey et al ., ). Finally, we recently showed that truncation of the CaS receptor after R 866 resulted in a complete inability of the receptor to stimulate Ca 2+ i mobilization, whereas IP accumulation was reduced, but maintained (Goolam et al ., ). In the same study, mutations in intracellular loops 2 and 3 greatly impaired IP accumulation, but had a weaker affect on Ca 2+ i mobilization.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, although both Ca 2+ o and L‐phenylalanine stimulated Ca 2+ i mobilization in CaS receptor‐transfected HEK293 cells, only Ca 2+ o promoted IP accumulation and diacylglycerol production (Rey et al ., ). Finally, we recently showed that truncation of the CaS receptor after R 866 resulted in a complete inability of the receptor to stimulate Ca 2+ i mobilization, whereas IP accumulation was reduced, but maintained (Goolam et al ., ). In the same study, mutations in intracellular loops 2 and 3 greatly impaired IP accumulation, but had a weaker affect on Ca 2+ i mobilization.…”
Section: Discussionmentioning
confidence: 97%
“…(19) Cell surface expression by ELISA Quantification of total and cell surface expression was completed using an ELISA-based assay that has been previously published. (20)…”
Section: Generation Of Cell Linesmentioning
confidence: 99%
“…The human CaSR is encoded by the CASR gene located on chromosome 3q21.1 and consists of: an extracellular domain, which binds Ca 2+ e and mediates receptor dimerization; seven transmembrane domains (TMDs); and an intracellular domain, which is involved in activation of downstream signaling effectors such as G proteins and phospholipase C (PLC) (2, 3). The CaSR stimulates two major signal transduction cascades.…”
Section: Introductionmentioning
confidence: 99%